2015
DOI: 10.1016/j.jmb.2015.07.022
|View full text |Cite
|
Sign up to set email alerts
|

How Myxobacteria Cooperate

Abstract: Prokaryotes often reside in groups where a high degree of relatedness has allowed the evolution of cooperative behaviors. However, very few bacteria or archaea have made the successful transition from unicellular to obligate multicellular life. A notable exception is the myxobacteria, in which cells cooperate to perform group functions highlighted by fruiting body development; an obligate multicellular function. Like all multicellular organisms, myxobacteria face challenges in how to organize and maintain mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 113 publications
(188 reference statements)
0
66
0
Order By: Relevance
“…Future studies in M. xanthus will need to test whether developmental lysis is a result of a toxin-antitoxin system, cell competition, and/or OME function. Previously, it was shown that OME leads to beneficial outcomes (13,40). Here, OME was found to lead to adversarial interactions, which is a typical response for bacterial cell-cell transfer systems.…”
Section: Discussionmentioning
confidence: 75%
“…Future studies in M. xanthus will need to test whether developmental lysis is a result of a toxin-antitoxin system, cell competition, and/or OME function. Previously, it was shown that OME leads to beneficial outcomes (13,40). Here, OME was found to lead to adversarial interactions, which is a typical response for bacterial cell-cell transfer systems.…”
Section: Discussionmentioning
confidence: 75%
“…According to the current model of fruiting body morphogenesis (Søgaard-Andersen et al, 2003), genes that are specifically expressed in sporulating cells depend on aggregation of cells into mounds. In addition, we have demonstrated the absence of McuA in glycerol-induced spores, where sporulation is uncoupled from cell aggregation (Cao, P. et al, 2015). Therefore, a possible explanation for delayed expression of mcuABC in DMXAN3487 is that it might be due to defective cell aggregation.…”
Section: Identification Of Mxan3487 As a Gene That Impacts Mcuabc Expmentioning
confidence: 81%
“…xanthus is a gliding bacterium that possesses two motility systems, the adventurous (A)-and social (S)-motility systems (Cao, P. et al, 2015;Islam & Mignot, 2015), both of which are necessary for aggregation of cells into mounds. To assess A-and S-motility in the DMXAN3487 strain, motility was tested on soft (0.5 %) agar, which favours S-motility, and hard (1.5 %) agar, which favours A-motility (Shi & Zusman, 1993).…”
Section: Identification Of Mxan3487 As a Gene That Impacts Mcuabc Expmentioning
confidence: 99%
“…OME is a process by which myxobacteria transiently fuse their outer membranes and exchange their outer membrane proteins and lipids (Figure 5 a ) (13). OME is initiated when two cells make contact on a solid surface (101).…”
Section: Bacterial Kin Recognitionmentioning
confidence: 99%